Petrographic Characterization of Raw Material Sources at Oldupai Gorge, Tanzania - Favreau, Julien; Soto, María; Nair, Rajeev; Bushozi, Pastory M.; Clarke, Siobhán; DeBuhr, Christopher L.; Durkin, Paul R.; Hubbard, Stephen M.; Inwood, Jamie; Itambu, Makarius; Larter, Fergus; Lee, Patrick; et al. (Frontiers in Earth Science, 2020)
Oldupai Gorge is located within the Ngorongoro Conservation Area, a UNESCO World Heritage Site in northern Tanzania along the western margin of the East African Rift System. Oldupai’s sedimentary record contains inter-stratified stone tool industries associated with the Earlier, Middle, and Later Stone Age. While diachronic technological change is perceptible, the totality of locally available rocks remained largely unchanged through time. Here, thin section petrography, Scanning Electron Microscopy-Energy Dispersive X-Ray Spectroscopy, and Electron Probe Micro Analysis were employed to characterize source lithologies in the Oldupai region. One of our goals was to determine if outcrops have rock types with unique mineral assemblages amenable for sourcing lithic artifacts. Petrographic analysis of sixty-two lithologic samples collected in primary and secondary positions reveal discriminatory differences. More precisely, five outcrops have quartzites with unique mineral assemblages, five outcrops have meta-granites with unique mineral assemblages, Engelosin phonolite samples are texturally and mineralogically unique, and magmatic samples recovered in secondary position may be sourced to their volcanic center. Our results demonstrate it is feasible to discriminate source materials using mineralogy, which implies that sourcing lithic artifacts is possible. For proof of concept, we assign the source/s of previously described fuchsitic quartzite artifacts from three archaeological sites at Oldupai to two nearby outcrops. Additional archaeological testing will allow researchers to glean new understandings of hominin behavior and stone procurement in the Oldupai paleobasin.